Identifying a human rights–based approach to obesity for States and civil society. (12th July 2019) - Patterson, David; Buse, Kent; Magnusson, Roger; Toebes, Brigit
Summary: Obesity and its comorbidities pose daunting challenges to global health and development in the 21st century. This paper reviews some commonalities between obesity and another global health challenge, the pandemic of human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS). International human rights law was an important catalyst for civil society movements that helped to overcome inertia and generate political will for State action in response to HIV and AIDS. Drawing on the HIV experience, the authors propose a conceptual model for a human rights–based response to obesity founded on the twin pillars of State obligations and civil society engagement. Framing States' obligations to address the global obesity pandemic as a matter of international law, informed by the examples of the United Nations "International Guidelines on HIV/AIDS and Human Rights" and the General Comments of the United Nations human rights treaty bodies on HIV and AIDS, provides a normative framework to guide State actions and opportunities to engage the extensive accountability mechanisms of the United Nations international human rights system. In addition, it provides civil society organizations with the language and tools to demand State action on obesity. The authors call for similar authoritative guidance for States on the application of international human rights law to obesity.